Impact of investment subsidy allocation schemes on levelized costs of renewable electricity-water systems in rural West Africa - Wilhelm Kuckshinrichs; Holger Schlör; Boubacar Ibrahim; Florian Siekmann; Sandra Venghaus (Energy Nexus)
Access to electricity and drinking water are among the main obstacles in rural West Africa. They could be mitigated by implementing PV systems with battery storage and electrical water pumping systems. To assess the impacts of electricity supply in Dar Es-Salam village, a rural West African community, the economics of a PV system with battery storage and electrical water pumping are scrutinized. These systems will facilitate electricity and water access and provide the village with uninterrupted supply. Within the rural context, electricity can be used for direct residential consumption and to operate an electric water pumping system to supply clean drinking water to the households, making it an integrated, linearly linked PV/battery and water pumping system. As access to financial resources illustrates another constraint, especially in the context of West Africa and the Sahel region, the paper further assesses impacts of an investment costs subsidy on the economics of electricity and water. By examining different allocation schemes of a constrained investment costs subsidy, the paper estimates their impact on the Levelized Costs of Electricity and Water, compares these results with the current state costs reported by local villagers, and identifies a superior subsidy allocation scheme. In our case, allocating the investment costs subsidy to the PV/battery system is identified as the superior allocation scheme. This is due to the high upfront PV/battery costs in relation to the water system but also reflects the villagers’ preferences as to electricity and water costs. Based on the case data for Dar Es-Salam village, the Levelized Cost of Electricity and of Water, respectively, resulted to 0.210€/kWh and 0.520 €/m3, without subsidy. A subsidy of approximately 2/3 of the total investment costs and allocating the subsidy to the PV/battery system offers to drastically reduce the Levelized Costs for Electricity and Water to 0.045€/kWh and 0.306 €/m3, respectively.